PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISIONS TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA PADA PELAJARAN BIOLOGI DI KELAS X SMK NEGERI 2 BANAWA - Alwin, Alwin (JSTT, 2015)
This study aims to find out the dfferences between motivation and learning outcomes of the students who get STAD learning model and conventional learning on Biology lesson of the Ten grade students of SMK 2 Banawa. The sample consisted of 64 students in two groups: 32 students as the experimental group and 32 students as the control group. The data were drawn from questionnaires, tests, and observation of teachers and students as well as record of events. The primary data were taken from the questionnaire and written test. The questionnaire  was  used  to  get  the  students’ motivation and the  test  was  used  to  assess  the  students’  learning  outcomes.  The observation sheets, record of events and interview guide were used to get supporting data. The primary data were analyzed by using N-gain test of pre-test and post-test. The significance was deterinined by using t-test of the two independent samples. The experimental and control groups were divided into upper, middle and bottom based on the pre-test and each group was determined by the N-gain learning aoutcomes. It was found that the middle group of the experimental class obtained the highest N-gain while the lower group of the control class obtained the highest N- gain. Based on the  result  of  the t-test using a significance of 0.05 for  Df = 62, it  is  concluded  that  1) there is a significant difference of motivation between the  students who got STAD learning  and  those who had conventional learning, 2) there is a significant difference of learning outcomes between the students who  got  STAD  learning  and  those  who had conventional learning.